Photophobia in migraine: an interictal PET study of cortical hyperexcitability and its modulation by pain. Issue 9 (30th June 2010) - Boulloche, Nicolas; Denuelle, Marie; Payoux, Pierre; Fabre, Nelly; Trotter, Yves; Géraud, Gilles
Abstract : Objective: Photophobia is an abnormal sensitivity to light experienced by migraineurs and is perhaps caused by cortical hyperexcitability. In clinical studies, an inter-relation between light perception and trigeminal nociception has been demonstrated in migraineurs but not in controls. The purpose of the study was to verify this interaction by functional imaging. Methods: The authors used H2 O 15 positron emitting tomography (PET) to study the cortical responses of seven migraineurs between attacks and the responses of seven matched control subjects to luminous stimulations at three luminance intensities: 0, 600 and 1800 Cd/m 2 . All three intensities were both with and without concomitant trigeminal pain stimulation. In order to facilitate habituation, the stimulations were started 30 s before PET acquisitions. Results: When no concomitant pain stimulation was applied, luminous stimulations activated the visual cortex bilaterally in migraineurs (specifically in the cuneus, lingual gyrus and posterior cingulate cortex) but not in controls. Concomitant pain stimulation allowed visual cortex activation in control subjects and potentiated its activation in migraineurs. These activations by luminous stimulations were luminance-intensity-dependent in both groups. Concomitant stimulation by pain was associated with activation of the posterior parietal cortex (BA7) in migraineurs and controls. Interpretation: The study shows the lack of habituation and/or cortical hyperexcitability to light in migraineurs. Moreover, the activation by light of several visual cortex areas (including the primary visual cortex) was potentiated by trigeminal pain, demonstrating multisensory integration in these areas.